The influence of culture on the communicative style of students in a Malaysian Secondary School - Thilagha Jaganathan,; Manjit Kaur, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2003)
This study investigates the influence of culture on the communicative style of students in a Malaysian school. It focuses on the relationship between cultural orientation and anxiety uncertainty management and language usage. Data were collected from 20 Chinese and Indian students from a Malaysian secondary school through a set of questionnaire to look into the cultural orientation and to identify its influence on the students' communicative style. The results indicate that the cultural orientation among the Chinese and Indian students vary on a continuum from high individualistic orientation to high collectivistic orientation. There is an almost equal distribution of individualists and collectivists among the Chinese students while there are more collectivists among the Indian students. The relationship between cognitive (uncertainty) and affective (anxiety) factors and the two selected aspects of language (beliefs about talks and direct-indirect communication) do not reciprocate indicating that other factors like personality, individual values and self-constructs influence one's communicative style. The collectivists on the other hand also exhibit similar relationship. The results contradict with the general characteristics of the individualistic and collectivistic orientation and recent work linking it with AUM theory. Theoretical implications are discussed.